APOBEC3, TRIM5α, and BST2 polymorphisms in healthy individuals of various populations with special references to its impact on HIV transmission. (January 2022) - Singh, HariOm; Jadhav, Sushama; Arif Khan, Abdul; Aggarwal, Shubham K.; Choudhari, Ranjana; Verma, Sheetal; Aggarwal, Sumit; Gupta, Vivek; Singh, Amita; Nain, Sumitra; Maan, Harjeet Singh
Abstract: AIDS restriction genes (ARGs) like APOBEC3, TRIM5α, and BST2 can act as immunological detectors of the innate protective mechanism of the body. ARGs influence the course of viral pathogenesis and progression of the disease. The infection caused by different viruses including HIV activates the innate immune receptors leading to production of proinflammatory cytokines, interferons and signals that recruit and activate cells involved in the process of inflammation following induction of adaptive immunity. Differential expression of genes involved in viral infection decide the fate and subsequent susceptibility to infection and its clinical outcome. Nevertheless, comprehensive reports on the incidence of genetic polymorphism of APOBEC3s, TRIM5α, and BST- 2 in the general population and its association with pathological conditions have not been described well. Therefore, the occurrence of APOBEC3, TRIM5α, and BST2 polymorphism in healthy individuals and its impact on HIV transmission was analyzed. We conducted an extensive search using the several databases including, EMBASE, PubMed (Medline), and Google Scholar. APOBEC3-D, -F, -G, and -H out of the seven human APOBEC3s, help in the control of viral infection. Amongst various restriction factors, TRIM5α and BST-2 also restrict the viral infection followed by the development of the disease. In the current review, a brief account of the polymorphism in the APOBEC3G, TRIM5 α, and BST2 genes are explored among different populations along with the interaction of APOBEC 3G with Vif protein . Furthermore, this review specifically focus on ARGs polymorphism ( APOBEC3G, TRIM5α, and BST2 ) associated with HIV transmission. Highlights: Study of AIDS restriction genes polymorphism may help to screen the susceptible population for the acquisition of HIV-1. APOBEC3G  variants analysis needs to be studied in detail. Host restriction factors might play a potential role and warrant investigation into therapeutic strategies